Antenatal care as a means to increase participation in the continuum of maternal and child healthcare: an analysis of the poorest regions of four Mesoamérican countries - Claire R. McNellan; Emily Dansereau; Marielle C. G. Wallace; Danny V. Colombara; Erin B. Palmisano; Casey K. Johanns; Alexandra Schaefer; Diego Ríos-Zertuche; Paola Zúñiga-Brenes; Bernardo Hernandez; Emma Iriarte; Ali H. Mokdad (BMC, 2019)
Abstract Background Antenatal care (ANC) is a means to identify high-risk pregnancies and educate women so that they might experience a healthier delivery and outcome. There is a lack of evidence about whether receipt of ANC is an effective strategy for keeping women in the system so they partake in other maternal and child interventions, particularly for poor women. The present analysis examines whether ANC uptake is associated with other maternal and child health behaviors in poor mothers in Guatemala, Honduras, Nicaragua, and Mexico (Chiapas). Methods We conducted a cross-sectional survey of women regarding their uptake of ANC for their most recent delivery in the last two years and their uptake of selected services and healthy behaviors along a continuity of maternal and child healthcare. We conducted logistic regressions on a sample of 4844 births, controlling for demographic, household, and maternal characteristics to understand the relationship between uptake of ANC and later participation in the continuum of care. Results Uptake of four ANC visits varied by country from 17.0% uptake in Guatemala to 81.4% in Nicaragua. In all countries but Nicaragua, ANC was significantly associated with in-facility delivery (IFD) (Guatemala odds ratio [OR] = 5.28 [95% confidence interval [CI] 3.62-7.69]; Mexico OR = 5.00 [95% CI: 3.41-7.32]; Honduras OR = 2.60 [95% CI: 1.42-4.78]) and postnatal care (Guatemala OR = 4.82 [95% CI: 3.21-7.23]; Mexico OR = 4.02 [95% CI: 2.77-5.82]; Honduras OR = 2.14 [95% CI: 1.26-3.64]), but did not appear to have any positive relationship with exclusive breastfeeding habits or family planning methods, which may be more strongly determined by cultural influences. Conclusions Our results demonstrate that uptake of the WHO-recommended four ANC visits has limited effectiveness on uptake of services in some poor populations in Mesoamérica. Our study highlights the need for continued and varied efforts in these populations to increase both the uptake and the effectiveness of ANC in encouraging positive and lasting effects on women's uptake of health care services.